2021
DOI: 10.3389/fnmol.2021.665085
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gene Expression Patterns of Ion Channels and Cytokines in Rat Primary Sensory Neurons During Development of Bone Cancer and Cancer Pain

Abstract: Cancer and cancer pain processes a major clinical challenge and the underlined mechanisms of pathogenesis remain elusive. We examined the specific changes in the transcriptomic profiles in the dorsal root ganglion (DRG) neurons of rats with bone cancer and bone cancer pain (BCP) using RNA sequencing technology. The bone cancer and BCP was induced by tumor cells implantation (TCI) into the tibia bone cavity in adult female rats. One week after treatment, TCI caused up- and down-regulation of thousands of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It has been reported that the development of bone cancer pain was accompanied by the expression of many genes in peripheral and central nervous system were changed. [16][17][18][19] Some researchers also found the changes of bone cancer pain gene expression profile by transcriptome sequencing. Some genes for the progression of pain hypersensitivity have also been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the development of bone cancer pain was accompanied by the expression of many genes in peripheral and central nervous system were changed. [16][17][18][19] Some researchers also found the changes of bone cancer pain gene expression profile by transcriptome sequencing. Some genes for the progression of pain hypersensitivity have also been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting data were quality-controlled and analyzed using bioinformatics methods. The rest samples were stored at -80°C [44][45][46].…”
Section: Tissue Sampling Rna Extraction and Sequencingmentioning
confidence: 99%
“…The incidence of chronic pain after surgical cancer treatment varies signi cantly with the type of cancer, treatment method, age, inherited variability, and psychiatric factors [21] . Oncogenes have now been found to be associated with the development of cancer with pain [22] . The ndings on pain-related genes in cancer patients can provide a reference for the development of the target drugs for tumor therapy, which is of great signi cance for alleviating pain and improving the quality of life of cancer patients [23] .…”
Section: Introductionmentioning
confidence: 99%